Expecting the Unexpected / Selecting the Right Primary Packaging for Injectable Formulations - Withers Nikki (Russel Publishing Ltd, 2019)
Building a Business Case for Modernising Microbiological Environmental Monitoring, What Brexit will Mean for Non-EU Countries: A Focus on Challenges for the ASEAN Region, Process and Analytical Method Elements of a Well-Defined Filing Control Strategy.